Ai Weiwei's Fairytale: a unique social engagement. Issue 1 (2nd January 2017) - Zhou, Yanhua
Abstract: Art as a social engagement in the West can be dated back to the history of avant-garde art starting from the end of nineteenth century. Rooted in his own cultural background, Chinese artist Ai Weiwei's socially engaged art project "Fairytale is more complex than the avant-garde strategy. The work Fairytale established a structure – "1=1, 001". That means on the one hand, the participants can be easily regarded everywhere in Kassel as 1, 001 mobile works of art. All of them contribute to an entire work. In other words, the 1, 001 people consist of one work. On the other hand, everyone is dealing with their personal issues independent of art. In this sense, the entire work can be divided into 1, 001 personal experiences. This structure is based on three principles of Chinese philosophy Taoism – the duality between Yin and Yang, the dynamism between Yin and Yang, and the concept of "uselessness". Positioning Fairytale within both Western theoretical as well as Chinese philosophical contexts, this essay is to analyze how Chinese philosophy shaped Ai's strategy of social engagement and his cultural identity – Chineseness.